Abciximab Suppresses the Rise in Levels of Circulating Inflammatory Markers After Percutaneous Coronary Revascularization - Lincoff, A.Michael; Kereiakes, Dean J.; Mascelli, Mary A.; Deckelbaum, Lawrence I.; Barnathan, Elliot S.; Patel, Kamlesh K.; Frederick, Bart; Nakada, Marian T.; Topol, Eric J. (Circulation (New York, N.Y.), 2001)
Background — Previous investigators have shown that systemic markers of inflammation may be increased in patients with acute ischemic syndromes or after percutaneous coronary revascularization and that persistent elevation in these markers is predictive of excess risk of subsequent adverse cardiac events. By virtue of its cross-reactivity with the glycoprotein IIb/IIIa, avβ3, and αMβ2 receptors, abciximab may reduce inflammatory processes. Methods and Results — Assays for the inflammatory markers C-reactive protein, interleukin-6, and tumor necrosis factor-α were performed on serum samples obtained from 160 patients in a placebo-controlled, randomized trial of abciximab during angioplasty. Eighty patients each had received a placebo or abciximab bolus plus a 12-hour infusion. Serum samples were drawn at baseline (before revascularization), 24 to 48 hours after study drug administration, and 4 weeks after study drug administration. Between baseline and 24 to 48 hours, the increase in C-reactive protein was 32% less in patients receiving abciximab than placebo ( P =0.025); the rise in interleukin-6 levels was 76% less in the abciximab group ( P <0.001); and the rise in tumor necrosis factor-α levels was 100% less with abciximab therapy ( P =0.112). By 4 weeks, most marker levels had returned to baseline, with no significant differences between placebo and abciximab groups. Conclusions — Systemic markers of inflammation increase in the first 24 to 48 hours after angioplasty, but the magnitude of that rise is diminished by periprocedural abciximab. Some of the long-term clinical benefit derived from this agent may be related to an anti-inflammatory effect.